Establishing recommendation trust relationships for internetwares. - Wang, Yuan (Software engineering notes.)
Internetware is a kind of significant emerging software systems built upon the coordination of autonomous, heterogeneous, and distributed software entities in the Internet. For the openness and dynamism of Internetwares, there are no central controllers existing to choose reliable software entities for them. Recently some distributed systems apply recommendation as the evidence to choose reliable entities, which may be a new approach suitable for internetwares. However, how to establish the recommendation trust relationships (RTR) among entities in the Internet dynamically is a very hard problem. This paper proposes an approach based on the relevant experiences to establish RTR among software entities dynamically during the runtime of internetwares. The main work includes: (1) providing a general approach to quantify trust and a description for experiences; (2) presenting an approach to evaluate recommendations based on the idea of hypothesis testing in statistics; (3) evolving the RTR based on the evaluations by considering history information and information quantity of interactions. It will be a beneficial contribution to the reliability and evolution of internetwares. A simulation is conducted to verify the rationality and validity of the approach at the end of the paper.